PERKEMBANGAN FIKIH PADA MASA BERAKHIRNYA MADHHAB - Nadhifah, Nurul Asiya (The Indonesian Journal of Islamic Family Law, 2014)
Abstract: This article discusses the development of Islamic jurisprudence at the expiration of Islamic thought which known as a taqlid period, i.e. the stagnation and static period that lasted from the mid-fourth century of Hijriyah (351 H). The growth of taqlid mentality in this period is due to several factors, the internal and external factors. Among these factors are social and political instability, legal definition of Islamic thought, fanaticism to certain Islamic thought, weakening the spirit of ijtihad, and closure of the gate of ijtihad. Currently, the Muslim scholarsâ activity is summarizing the classical books (mukhtasar). Among the many classical books caused many questions, then they started to compile the book explanations. Despite this circumstance, there are still some people who remain dynamic and creative thinking, even if they are dealing with the challenge of the ruler, who are ready to throw into prison for their firm stance. Among the scholars who are attempting to break the rigidity of this period are Shaykh al-Islam Ibn Taymiyyah (d. 728 AH) and Ibn Qayyim al-Jauziyah (d. 751 AH).Abstrak: Artikel ini membahas tentang perkembangan fikih pada masa berakhirnya madhhab yang biasa dieknal dengan periode taqlÄ«d, yaitu periode kebekuan dan statis yang berlangsung mulai pertengahan abad empat hijriah (351 H). Tumbuh dan berkembangnya mentalitas taqlÄ«d pada periode ini disebabkan oleh beberapa faktor, baik internal atau eksternal. Di antara sebagian kecil faktor tersebut ialah; Instabilitas sosial politik, rumusan hukum madhhab fiqh dianggap sudah pari purna, fanatisme bermadhhab taâassub), melemahnya semangat ijtihad, dan tertutupnya pintu ijtihad. Aktifitas ulama dalam zaman ini antara lain menyusun ringkasan ringkasan kitab (mukhtasar). Di antara kitab mukhtashar ternyata banyak pulaÂ  yang menimbulkan pertanyaan, maka disusun pula kitab sharhnya (penjelasan). Meskipun demikian tidak menutup mata ada satu atau dua orang yang tetap berfikir dinamis dan kreatif sekalipun mereka berhadapan dengan tantangan tantangan dari para penguasa, yang siap menjebloskan ke dalam penjara karena keteguhan pendiriannya. Di antara ulama yang berupaya mendobrak kebekuan masa ini antara lain: Syaikh al-IslÄm Ibn Taimiyah (w. 728 H.) dan Ibn Qayyim al-Jauziyah (w. 751 H.).